Analisis Tindak Tutur Naskah Drama Nyanyian Kardus Karya Puntung CM. Pudjaji: Pragmatik - Sumantri, Liza Fathan (Multiverse: Open Multidisciplinary Journal, 2023)
This study aims to determine speech acts in pragmatics related to locutionary, illocutionary and perlocutionary. The source of the data in this study was the drama script Nyanyian Kardus by Puntung CM. Pudjadi which was published by Interlude with a thickness of 94 pages. The method used in this research is descriptive method. The instrument in this research is a documentation study. The data analysis technique is by reading, understanding the contents of the drama script, finding relevant sources of information, making observations, analyzing data, drawing conclusions from the research results. The results obtained are: (a) locutionary speech acts related to the meaning of words that explain or inform something clearly without any other purpose or meaning in it. (b) illocutionary speech acts related to the hidden meaning of a word or statement. (c) perlocutionary speech acts related to someone's meaning or attitude towards a sentence that is heard or read.